BOTANICAL AND BIOLOGICAL STUDIES OF PLECTRANTHUS TENUIFLORUS (VATKE) AGNEW. (LAMIACEAE) GROWING IN SAUDI ARABIA: Life Science-Botany - NAHED M. WALY; SABAH H. EL GAYED (International Journal of Life Science and Pharma Research, 2012)
The macro- and micro morphology of leaves and stem of Plectranthus tenuiflorus (Vatke) Agnew growing in Saudi Arabia were described and illustrated for their identification in both entire and powdered forms, in order to contribute for the medicinal plant identification. In Vitro antiprotozoal activities of methanol Extract against Malaria, Leishmaniasis, Sleeping Sickness and Chagas Disease were evaluated against Plasmodium falciparum, Leishmania infantum, Trypanosoma brucei brucei and T. cruzi respectively as well as toxicity against MRC-5 fibroblast cells. The result showed promising activity against P. falciparum and moderate, antiprotozoal activity against T. cruzi and Leishmania infantum and mild activity against T. bruci.In vitro antioxidant and free radical scavenging activity of the methanol extract was determined by spectrophotometric methods. The result indicate that the extract has a promising antioxidant activity and could be considered as potential source among the antioxidants natural origin